Efektivitas Pemanfaatan Quizizz dalam Meningkatkan Motivasi Belajar Matematika Siswa Kelas X di SMA Negeri 1 Gerung - Ahmad Fauzi; Siti Rahmawati; Lalu Hadi Saputra (Educational Note, 2026)
This study aims to analyze the increase in mathematics learning motivation among Grade 10 students at SMA Negeri 1 Gerung following the use of the Quizizz platform as an interactive learning medium. The background of this study is based on the relatively low level of students’ motivation to participate in mathematics learning, which affects their engagement and learning outcomes. This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design without a control group for comparison. The sample consisted of 36 students from one class selected through purposive sampling based on the criterion of having the lowest level of classroom engagement compared with other Grade 10 classes. Data were collected using a learning motivation questionnaire that had met validity and reliability requirements and were subsequently analyzed using descriptive statistics and a paired-sample t-test. The results showed that the students’ mean motivation score increased from 68.42 in the pretest to 82.75 in the posttest. The paired-sample t-test yielded a value of t(35) = −11.842 with a significance level of 0.000 (p < 0.05), while the effect size (Cohen’s d) was 1.97, which is categorized as very large. Given that the research design did not include a control group, these findings should be interpreted as preliminary evidence of an increase in learning motivation associated with the use of Quizizz and cannot yet be generalized as definitive evidence of a causal relationship. The implications of this study suggest that integrating gamification-based digital technology has the potential to serve as an alternative learning strategy for creating more engaging learning experiences, although further investigation using stronger research designs is needed.